Genetic diversity of Couratari multiflora and Couratari guianensis (Lecythidaceae): Consequences of two types of rarity in central Amazonia - Lepsch-Cunha, Nadja; Kageyama, Paulo Yoshio; Vencovsky, Roland (Biodiversity and Conservation, 1999)
We quantified the within-population genetic variation of Couratari multiflora and C. guianensis, two tree species found in 'terra firme' forests of central Amazonia. Both species have some ecological features in common, but they differ in population abundance across their geographic ranges. While C. multiflora has been found only in low-density populations in all sites studied to date, C. guianensis is relatively common in some sites and very scarce in others. In a 400-ha plot, we found 41 and 29 adults of C. multiflora and C. guianensis, respectively. Twenty-two saplings of C. guianensis and 103 seedlings of C. multiflora were also examined. The mean expected heterozygosities (Hem) of seedlings and adults of C. multiflora were 0.431 and 0.436, and the mean fixation indices (F(m)), 0.114 and 0.176, respectively. For C. guianensis, saplings and adults presented H(em) equal to 0.425 and 0.429, and the F(m) were 0.393 and 0.527, respectively. These low-density populations of two congeneric species did not differ in terms of genetic diversity, but rather they differed in terms of mean observed heterozygosity (H(om)), and therefore F(m). The species with variable population density had lower Horn and greater F(m) relative to the species that is always found in low-density.
Keywords: Genetic Variation; Genetics, Population; Rarity; South America; Couratari Guianensis; Couratari Multiflora